2001
DOI: 10.1074/jbc.m104446200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA Replication and Induction of S Phase Cell Cycle Arrest by G-rich Oligonucleotides

Abstract: The discovery of G-rich oligonucleotides (GROs) that have non-antisense antiproliferative activity against a number of cancer cell lines has been recently described. This biological activity of GROs was found to be associated with their ability to form stable G-quartet-containing structures and their binding to a specific cellular protein, most likely nucleolin (Bates, P. J., Kahlon, J. B., Thomas, S. D., Trent, J. O., and Miller, D. M. (1999) J. Biol. Chem. 274, 26369 -26377). In this report, we further inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
161
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(172 citation statements)
references
References 60 publications
9
161
0
1
Order By: Relevance
“…Synchronization of Cells-Cells were synchronized using the serum starvation method (16). Briefly, A549 and Calu-1 cells were plated in complete medium (DMEM or RPMI 1640) containing 10% FBS, at a density of 5 Ï« 10 4 cells/well in 6-well plates and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Synchronization of Cells-Cells were synchronized using the serum starvation method (16). Briefly, A549 and Calu-1 cells were plated in complete medium (DMEM or RPMI 1640) containing 10% FBS, at a density of 5 Ï« 10 4 cells/well in 6-well plates and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Slides were washed with PBS and incubated in permeabilization solution (0.1% Triton X-100, 0.1% sodium citrate) for 2 min on ice, washed twice with PBS, and dried. Samples were stained as previously described (29). Briefly, 50 l of TUNEL reaction mixture (Roche) was added to each sample and slides were incubated in the dark in a humidified chamber for 60 min at 37°C, then washed three times with PBS and observed as above.…”
Section: Methodsmentioning
confidence: 99%
“…GRO showed an arrest effect of the cell cycle predominantly in S phase. 38) Joe et al found resveratrol caused an increase of cells in the S phase and a corresponding decrease of cells in the G 1 and G 2 -M phases in HCE7, MCF7, SW480, and HL60 cells. But in Bic-1 cell, resveratrol treatment led to G 1 -phase arrest, and resveratrol did not appear to alter the cell cycle distribution in Seg-1 cell.…”
Section: Discussionmentioning
confidence: 99%